Disorienting Suspense and Narrative Turns of the Screw in Mircea Eliade’s Miss Christina - Ileana ORLICH (Cultural Intertexts, 2023)
This interpretation of Miss Christina results from my personal text-oriented criticism in reevaluating the story as well as from my own response to contemporary cultural shifts in recontextualizing major literary works such as Henry James’s The Turn of the Screw. I consider Mircea Eliade’s comments about writing Miss Christina as a ghost story in which a young woman returns to the world of the living as a vampire and desires to be loved by a mortal to be a narrative challenge for the astute reader, a provocation similar in a comparative context to James’s disclaimers about The Turn of the Screw as a mere ghost story. I note that the character doubling of Miss Christina with the beautiful young girl Simina and Egor’s failed attempt to impose his own narrative of an unrealizable romance with the vampire and of his search for the truth about the girl Simina are behind the story’s dynamic in an oscillating drama that highlights problematic hallucinations; they haunt the text and the Bărăgan plain as much as they haunt Egor’s own mind. Finally, I argue that the story’s doubling vision becomes a way of representing the horror of Egor’s conflicted sexuality and of his search for moral certainty.